The Influence of Regional Original Income, Capital Expenditures and Labor Force Participation Levels on Gross Regional Domestic Product (GRDP) in Districts/Cities of West Nusa Tenggara Barat (NTB) in 2018-2022 - Muh. Andi Wirya Sintanu; Mansur Afifi; Karismawan , Putu (Tinta Emas Institute, 2024)
This research analyzes the influence of Regional Original Income (PAD), Capital Expenditures, and Labor Force Participation Level (TPAK) on the Growth of Gross Regional Domestic Product (GRDP) in the Districts/Cities of Nusa Tenggara Barat Province (NTB). Data was collected from October 2023 to January 2024 and analyzed using a quantitative approach and panel data regression. The results show that PAD has a positive and significant influence on GRDP, while Capital Expenditure and TPAK are not significant. The implication is that regional governments need to optimize policies and use of capital expenditure to support GRDP growth. In addition, efforts are needed to increase labor force participation in order to make a more significant contribution to regional economic growth. This research provides insight for policy makers and stakeholders regarding the factors that influence economic growth in NTB.